SISTEM INFORMASI PENERIMAAN DAN PENGELUARAN KAS MENGGUNAKAN VBA PADA CV SAGARA MOBILE - Aldona, Citra; Yuliman, Apit (Jurnal Mahasiswa Terapan, 2024)
This research is entitled "Cash Receipt and Expenditure Information System Using VBA on CV Sagara Mobile". The aim of this research is to design, implement and test a cash receipt and expenditure information system using VBA on CV Sagara Mobile. The method used is a qualitative research method using Waterfall system development. Data collection techniques use observation, interviews and literature study techniques. The results of this research analysis are companies that still use manual activities when entering transaction data and presenting data so that they are considered ineffective and inefficient. Therefore, the author carried out an analysis using the PIECES method. System design using VBA and using computerized data storage. This system can make it easier to enter data, create financial reports and maintain data security and accuracy. System implementation using VBA is equipped with automatic reports in the form of cash receipt report data and cash disbursement reports contained in the database, as well as using system testing with the BlackBox method and User Acceptance Test which shows very good results with a percentage of 84.5% based on testing on 5 respondents.